Subdirectly irreducible separable dynamic algebras - Pinto, Sandra Marques (2009)
A characterization of the subdirectly irreducible separable dynamic algebras is presented. The notions developed for this study were also suitable to describe the previously found class of the simple separable dynamic algebras.